Critical Speed Control for a Fixed Blade Variable Speed Wind Turbine - Morgan Rossander; Anders Goude; Sandra Eriksson (Energies, 2017)
A critical speed controller for avoiding a certain rotational speed is presented. The controller is useful for variable speed wind turbines with a natural frequency in the operating range. The controller has been simulated, implemented and tested on an open site 12 kW vertical axis wind turbine prototype. The controller is based on an adaptation of the optimum torque control. Two lookup tables and a simple state machine provide the control logic of the controller. The controller requires low computational resources, and no wind speed measurement is needed. The results suggest that the controller is a feasible method for critical speed control. The skipping behavior can be adjusted using only two parameters. While tested on a vertical axis wind turbine, it may be used on any variable speed turbine with the control of generator power.